The Influence of Diet and Exercise on the Physical Health of Affected Individuals with VCP Disease - Kimonis, Virginia; Hamorsky, Katherine; Surampalli, Abhilasha; Wencel, Marie; Khare, Manaswitha (International Journal of Biotechnology for Wellness Industries, 2014)
While there is no curative treatment for the Inclusion body myopathy, Paget disease of bone and/ or frontotemporal dementia (IBMPFD) disorder, it is worthwhile to investigate alternate therapies that may slow the progression of the disease and improve the quality of life in this patient population. Therefore, this study aims to evaluate the impact of diet and exercise changes on the Quality of Life questionnaire. We assessed data from the questionnaire in 30 individuals (mean age 50.86 years; range 27-65 years; 16 Males, 14 Females) that participated in the clinical study of Valosin Containing Protein (VCP) disease. Eleven affected individuals consumed a high fat/sugar diet and 15 low fat/sugar diet of 4.09±0.25 and 1.53±0.13 servings/day respectively. Eleven individuals reported not exercising and 12 reported moderate exercise of 2.44±0.74 hours/week. In this cohort we found significantly higher mean physical health domain score for all those who exercised (P=.02) and surprisingly in those who had a high fat/sugar diet (P=.01). In the high fat/sugar diet group there was a significantly greater ability to walk; greater perceived muscle strength in arms and legs (P=.03; P=.02 and P= .02 respectively). Therefore lifestyle changes with exercise training and a higher fat/ sugar diet may have a beneficial effect in affected individuals with VCP disease. Nevertheless, larger studies with further research are needed to confirm these preliminary studies before making clinical practice recommendations.